Play Therapy as a Counseling Guidance Service for Children Victims of Natural Disasters (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
Children affected by disasters often experience trauma, anxiety, or even post-traumatic stress disorder (PTSD), which can disrupt their emotional and social development. One method commonly used in Guidance and Counseling (BK) is Play Therapy, a therapy that uses play as a tool to help children express their feelings more easily. This article aims to comprehensively review the results of research published in the last five years (2020–2025) on the effectiveness of Play Therapy for children affected by disasters. The method used literature review using sources from various databases such as Google Scholar, ResearchGate, Garuda Kemdikbud. The review results indicate that Play Therapy is very helpful in reducing trauma symptoms, increasing coping skills, and supporting the psychosocial recovery of children affected by disasters. Several types of therapy that have proven effective include sand play therapy, group play therapy, and art-based play therapy. However, several challenges remain, such as a lack of facilities, limited training for counselors, and the ever-changing post-disaster situation. The implication is that schools and humanitarian organizations should provide specialized training for counselors and also encourage the inclusion of Play Therapy in trauma recovery programs after disasters